Feed-Forward Control Algorithm for Hybrid Energy Systems. (2015) - Nair, Parvathi; Deepa, K.
Abstract: The paper presents a comparative analysis of the control strategies that can be used for hybrid energy systems. In the system considered, solar energy and battery are the two input sources to the DC-DC converter. Due to the intermittent availability of solar energy, a control circuit needs to be designed for the voltage regulation of the hybrid energy system. A single input fuzzy logic controller can maintain the output voltage constant for variations in either Photovoltaic (PV) or battery voltage only. Hence a control strategy is proposed in this paper to accomplish output voltage regulation for variations in both PV and battery voltages. The comparison of the two control techniques is presented along with the simulation results.